2002
DOI: 10.1002/j.2162-6057.2002.tb01059.x
|View full text |Cite
|
Sign up to set email alerts
|

Can People Creative in Imagery Interpret Ambiguous Figures Faster than People Less Creative in Imagery?

Abstract: The purpose of the research study was to investigate whether people creative in imagery are better than people non‐creative in imagery at interpreting ambiguous figures. Creativity, in the imagery paradigm, is said to involve two processes: combinational play and discovery. Discovery plays a major role in creativity as it is the process of discerning, judging or interpreting the value of a mental construction. Furthermore, creative people have been said to be insightful thus supporting the proposition advanced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 25 publications
1
12
0
Order By: Relevance
“…<Insert Table 2 about here.> The results of Study 2 strongly indicate that production of unusual uses for familiar objects is linked to ease of figural reversal. The results are consistent with Riquelme's (2002) observation that production of unusual figures from component shapes was related to figural reversal ability.…”
Section: Task Scoringsupporting
confidence: 91%
See 1 more Smart Citation
“…<Insert Table 2 about here.> The results of Study 2 strongly indicate that production of unusual uses for familiar objects is linked to ease of figural reversal. The results are consistent with Riquelme's (2002) observation that production of unusual figures from component shapes was related to figural reversal ability.…”
Section: Task Scoringsupporting
confidence: 91%
“…The null results arose from studies with small Ns and so may be due to low statistical power. Riquelme (2002) found a significant relationship between performance on a visuo-spatial creative synthesis task (Finke & Slayton, 1988) and ease of detecting ambiguous figure reversals.…”
Section: Introductionmentioning
confidence: 94%
“…Results indicated that frequency of successfully check had a positive linear relationship with alternate uses task performance. In addition, there were also studies reporting that successful recognition of reversed ambiguous figures was associated with divergent thinking (Riquelme, ; Klintman, ; Wiseman et al., ). Moreover, Stoycheva (, ) suggested that ambiguity tolerance, the capacity to resist stereotypical reactions or premature solutions in complex, unusual, or novel situations, could cultivate an inquiring, persistent, and courageous creative attitude.…”
mentioning
confidence: 99%
“…Disambiguation is the ability to interpret ambiguous information in a sensible way, and it is considered one of the fundamental components of the creativity process (Riquelme, 2002; Wiseman et al, 2011). This is true in terms of art appreciation and when creating works of art (Zeki, 2008).…”
Section: Introductionmentioning
confidence: 99%